2017
DOI: 10.1007/698_2017_38
|View full text |Cite
|
Sign up to set email alerts
|

Soil Remediation by Electro-Fenton Process

Abstract: Soil remediation by electro-Fenton (EF) process has been recently proposed in literature. Being applied for solutions treatment, EF is mainly combined with soil washing (SW)/soil flushing (SF) separation techniques to remove the organic pollutants. The main criteria influencing the combined process have been identified as: (i) operating parameters (electrode materials, current density and catalyst (Fe 2+ ) concentration), (ii) the matrix composition (nature and dose of extracting agent, pH, complexity of SW/SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…Fenton's reagent (H 2 O 2 , Fe( ii )), initially described over a century ago, 4 produces highly reactive ˙OH radicals ( E 0 = 2.8 V/NHE) to begin a radical reactions chain (eqn (1)–(8)), 5,6 and destroys a variety of organic pollutants in water and soil 7–13 with high reaction rate constants of 10 8 to 10 11 M −1 s −1 . 14 The Fenton process is the oldest advanced oxidation process.Fe( ii ) + H 2 O 2 → ˙OH + Fe( iii ) + OH − , k 1 = 63–76 M −1 s −1 Fe( ii ) + ˙OH → Fe( iii ) + OH − , k 4 = (3–4.3) × 10 8 M −1 s −1 ˙OH + ˙OH → H 2 O 2 , k 7 = (4.2–5.5)×10 9 M −1 s −1 …”
Section: Introductionmentioning
confidence: 99%
“…Fenton's reagent (H 2 O 2 , Fe( ii )), initially described over a century ago, 4 produces highly reactive ˙OH radicals ( E 0 = 2.8 V/NHE) to begin a radical reactions chain (eqn (1)–(8)), 5,6 and destroys a variety of organic pollutants in water and soil 7–13 with high reaction rate constants of 10 8 to 10 11 M −1 s −1 . 14 The Fenton process is the oldest advanced oxidation process.Fe( ii ) + H 2 O 2 → ˙OH + Fe( iii ) + OH − , k 1 = 63–76 M −1 s −1 Fe( ii ) + ˙OH → Fe( iii ) + OH − , k 4 = (3–4.3) × 10 8 M −1 s −1 ˙OH + ˙OH → H 2 O 2 , k 7 = (4.2–5.5)×10 9 M −1 s −1 …”
Section: Introductionmentioning
confidence: 99%
“…As soil washing/flushing only transfers the pollution from solid to liquid matrix, there is a need for a post-treatment to remove the contaminants. In the past few years, advanced electrochemical treatment has appeared as a promising alternative to biological post-treatment, since those pollutants are barely biodegradable (Mousset et al, 2017).…”
Section: High Cod Load With Low Pollutant Contentmentioning
confidence: 99%
“…Table 9 presents the state of the art of electrochemical treatment of soil washing/flushing solutions. Generally, it is observed that organic pollutants represent only 1% to 5% of the total organic carbon fraction, the remaining part consisting mostly of the extracting agent, while the organic matter content extracted from soil is negligible (Mousset et al, 2017). Interestingly, using different families of extracting agents has shown to affect the electrochemical treatment efficiency.…”
Section: High Cod Load With Low Pollutant Contentmentioning
confidence: 99%
See 2 more Smart Citations